Symbolism In The Mosques of Mimar Sinan: Inscriptions, Meanings, and Architectural Order - Şimşek, Cemile Feyzan; Peker, Ali Uzay; Şener, Sinan Mert (Kadim, 2024)
Architectural spaces not only consist of structural elements but also bear traces from the period in which they were built. These traces can be religion, culture, economy, power, technology, abstract concepts, or symbols. Worship places, in particular, contain diverse symbols and indicators due to their mission. Mosques specific to the Islamic religion also have various symbolic elements besides their original architectural features. It is seen in history that these elements are included in mosque architecture with abstract ornaments and calligraphy. In the mosques of Mimar Sinan’s period, the inscriptions mainly consist of Qur’ān verses. These verses are placed on many architectural elements, starting from the dome. The study aims to systematically question and reveal the relationship between these verses and the architectural elements where they are placed using the semiotic method. Five mosques, the richest in terms of the epigraphy program, were selected as samples for the study. All the inscriptions in the mosques were identified on-site, and their accuracy was ensured by comparing them with sources related to the period. In this study, the symbolism of the inscriptions in Mimar Sinan’s mosques, which has not been revealed before, is presented uniquely for each architectural element by reading them through the inscriptions and structural elements.